2017
DOI: 10.1101/218719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of guard-cell ABA in determining maximal stomatal aperture and prompt vapor-pressure-deficit response

Abstract: 21Abscisic acid (ABA) is known to be involved in stomatal closure. However, its role in

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
(68 reference statements)
1
6
0
Order By: Relevance
“…These results suggest that the main role of basal ABA under SD conditions is to maintain the stomata closed during the night hours. This finding is consistent with previous data showing that endogenous ABA accumulates to a maximum during the dark period 19,36 , and with results showing that ABA-insensitive plants display more open stomata in the dark 37 . In addition, our results show that endogenous basal ABA is necessary for full stomatal closure during dusk, although other factor(s) are probably involved given that aba2 seedlings at ZT9 display more open stomata than Col-0 (~21 μm 2 compared to ~12 μm 2 ) (Fig.…”
Section: Resultssupporting
confidence: 93%
“…These results suggest that the main role of basal ABA under SD conditions is to maintain the stomata closed during the night hours. This finding is consistent with previous data showing that endogenous ABA accumulates to a maximum during the dark period 19,36 , and with results showing that ABA-insensitive plants display more open stomata in the dark 37 . In addition, our results show that endogenous basal ABA is necessary for full stomatal closure during dusk, although other factor(s) are probably involved given that aba2 seedlings at ZT9 display more open stomata than Col-0 (~21 μm 2 compared to ~12 μm 2 ) (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Defects in several ABA biosynthesis and ABA signaling mutants in Arabidopsis increase steady-state stomatal conductances and thus shift VPD responses to higher stomatal conductance values (5,37). Recent time-resolved stomatal conductance analyses have led to the model that the rapid stomatal conductance response to VPD elevation occurs in parallel to the ABA signaling pathway (5,34). A signaling pathway parallel to ABA signaling is the CO 2 signaling pathway (46).…”
Section: Resultsmentioning
confidence: 99%
“…Early studies on ABA-deficient (aba1-1) and ABAinsensitive (abi1-1 and abi2-1) mutants suggested that ABA and ABA signaling are not necessary for high VPD-induced stomatal closure (33). This is supported by the investigation of transgenic lines expressing a guard-cell-targeted dominant abi1-1 protein phosphatase, which showed a wild-type (WT)-like stomatal response to a rapid increase in VPD, including in time-resolved gas-exchange analyses (34). Overexpression of the Arabidopsis abi1-1 mutant allele in gray poplar, Populus x canescens (Aiton) Sm., exhibited a defect in steady-state stomatal conductance in response to a VPD increase (35).…”
Section: Significancementioning
confidence: 97%
See 1 more Smart Citation
“…Stomatal imprints were taken from adaxial and abaxial epidermises of glasshouse‐grown plants, as described in Yaaran et al . (2019). See Methods S1 for a detailed description.…”
Section: Methodsmentioning
confidence: 99%